Adaptive Weblog Post Filtering Based on User Browsing History - Farahmand Nejad, Ali; Kharazmi, Sadegh; Bayati, Shahabedin; Abolhassani, Hassan; Golmohammadi, Koosha (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
Weblogs are one of important Web-based services that establish the foundations of the Web 2.0. These days many companies propose free Weblog hosting and population services, because they realize that Weblogs are evolving to be a more topic based systems, and so they could be good places to gain more revenue. One of effective factors for gaining more revenue is blog popularity. Weblogs have posts that arranged chronologically with most recent first. Some of Weblog has many posts that cause difficulty in finding specific posts by each viewer. On the other hand unsuitable posts order can redouble this problem. This difficulty occasions reduction of Weblog popularity. As our researches on Farsi weblogs shown many viewers close some Weblog windows before completely loaded in their own Web browsers. Based on our research an important reason is the existence of vast amount of Weblog posts. Viewer interests can be beneficial if they utilize for adaptive filtering Weblogs and showing their contents. This paper represents an approach for filtering and reordering Weblog posts based on user’s browsing history Experimental results show that our filtering approach can improve Weblog popularity and can increases Weblog viewers.